Contrasting the influences of phosphate and phosphite on growth of Aspergillus niger - Wang, Ying; Ding, Kejin; Ji, Jiakai; Xu, Meiyue; Yan, Shihui; Fan, Yonghong; Yu, Dan; Li, Zhen (Frontiers in Microbiology, 2025)
Phosphite serves as an alternative phosphorus material in terrestrial ecosystems. Aspergillus niger (A. niger), a prominent phosphate-solubilizing fungus (PSF), facilitates phosphorus and leaches heavy metal ions via organic acids and enzymes. With the synergistic effect of phosphate materials, heavy metal ions can be effectively immobilized by A. niger to achieve remediation of contaminated soils. This study investigated the structural distinctions between phosphite and phosphate compounds by using ATR-IR and Raman spectroscopy, while concurrently assessing the physiological impact of phosphite on A. niger. After incubation with phosphite, the average fungal biomass and acid phosphatase activities were reduced by approximately 50% with respect to phosphate. These results demonstrated a significant inhibitory effect of phosphite on PSF functionality. This inhibition likely stems from fundamental differences in the molecular structures of phosphite and phosphate, which influence their biochemical interactions. The observed suppression underscores the limited evolutionary adaptation of organisms to phosphite detoxification or metabolic assimilation. Consequently, phosphate persists as the dominant bioavailable phosphorus form on Earth. Finally, this induces its geological abundance and the lower metabolic cost for assimilation.